Investigations on the Carrier Mobility of Cs2NaFeCl6 Double Perovskites - Jiyuan Xing; Yiting Zhao; Wei-Yan Cong; Chengbo Guan; Zhongchen Wu; Dong Liu; Ying-Bo Lu (Crystals, 2024)
Double perovskite materials have gradually become widely studied due to their potential applications in solar cells and other optoelectronic devices. We take Cs2NaFeCl6 as an example to investigate the carrier mobility with respect to the acoustic phonon and the optical phonon scattering mechanisms. By considering the deformation potential, carrier effective mass, and bulk modulus, the longitudinal acoustic (LA) phonon-determined mobilities for electrons and holes in Cs2NaFeCl6 are found to be μe = 2886.08 cm2 v−1 s−1 and μh = 39.09 cm2 v−1 s−1, respectively. The optical scattering mechanism involves calculating the Fröhlich coupling constant, dielectric constant, and polaron mass to determine the multiple polar optical (PO) phonon-scattering-determined mobilities, resulting in μe = 279.25 cm2 v−1 s−1 and μh = 21.29 cm2 v−1 s−1, respectively. By combining both interactions, the total electron mobility and hole mobility are determined to be 254.61 cm2 v−1 s−1 and 13.78 cm2 v−1 s−1, respectively. The findings suggest that the polarization of both electrons and ions, small coupling constant, and bulk modulus in Cs2NaFeCl6’s lattice make PO scattering a significant contribution to carrier mobility in this specific double perovskite, highlighting the importance of considering this in enhancing the optoelectronic properties of Cs2NaFeCl6 and other double perovskites.